Marketing of Food and Beverages to Children in the Eastern Mediterranean Region: A Situational Analysis of the Regulatory Framework - Al-Jawaldeh, Ayoub; Jabbour, Jana (Frontiers in Nutrition, 2022)
Marketing of food items high in added saturated and/or trans-fat, sugar, or sodium (HFSS) negatively affect consumption patterns of young children. The World Health Organization (WHO) advised countries to regulate the marketing of foods and non-alcoholic beverages to young populations. The aim of this manuscript is to provide a situational analysis of the regulatory framework of food marketing policies targeting children in the Eastern Mediterranean Region (EMR). A semi structured questionnaire was shared with the focal points in all EMR member states inquiring about the reforms and monitoring initiatives in place. Electronic databases were searched for relevant publications between 2005 and 2021. Results revealed that even though 68% of countries discussed the recommendations, progress towards WHO set goals has been slow with only 14% of countries implementing any kind of restrictions and none executing a com-prehensive approach. Reforms have focused on local television and radio marketing and left out several loopholes related to marketing on the internet, mobile applications, and cross border marketing. Recent monitoring initiatives revealed a slight improvement in the content of advertised material. Marketing remains largely for unhealthy products. This review identified the need to intensify the efforts to legislate comprehensive food marketing policies within and across EMR countries.